Use Powder Of Wood Ulin (Eusideroxylon Zwageri) For Mixed Materials Builders Head Bushing - Prantasi H. Tjahjanti; Eko Wahyono Setyawan (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2016)
Head bushing is part of the plastic sack-making machine components that process works always have friction between the bushing head cham causing wear and tear. This wear and tear leads to further damage to the components - components other spare parts. Head material is nylon pure solid has a melting point 350-425 ° C, but was unable to maintain its shape because happen frictions during the process of making plastic sack. Research to make head bushing by adding the powder of wood Ulin (Eusideroxylon Zwageri) as reinforcements and to do wear and tear. The results obtained show. that the optimum value of the powder composition wood ulin is 4% , with value of wear and tear 0,0544 mm/h with a time 96 hours 29 minutes 29 seconds. But overall, the addition powder of wood Ulin, cannot be used as ingredients of make head bushing, because value of wear and tear of head bushing without additive of powder of wood Ulin, more smaller than head bushing with additive powder wood Ulin.